Experimental study on the effect of microwave heating power on the drying behavior of onion slices - G Srinivas; G Bhanu Radhika; BVS Praveen (MethodsX, 2025)
Microwave drying has become a highly effective and energy-efficient technique for the processing of agricultural products, mainly onion slices. This method proves to be advantageous over traditional methods of drying like sun drying and hot-air drying, which are often accompanied by longer periods of drying time and quality loss in terms of color, texture, and nutrient content. Microwave drying allows moisture removal through volumetric heating and thus saves energy while preserving essential quality attributes. This study examines the effects of microwave power levels ranging from 200 W to 1000 W on the drying behavior and quality attributes of onion slices of different thicknesses. The results showed that higher microwave power levels enhance drying rates but may cause undesirable quality degradation, such as color changes and texture softening. Mathematical models were developed to predict instantaneous moisture content and drying kinetics, which are crucial for optimizing drying processes. The study highlights the need for microwave power balance, drying time, and slice thickness to preserve the quality of the product but increase the efficiency of drying. Findings can contribute to developing optimized microwave drying protocols to achieve improvements in energy efficiency, quality of the products, and sustainability in agricultural processing.➢Higher power levels increase efficiency but may degrade product attributes. ➢Texture analysis was conducted on onion slices dried at different microwave powers. ➢Color analysis of onion slices dried at different microwave power levels.